Neuroprotective and neuritogenic activities of Lignosus rhinocerotis (COOKE) ryvarden / Priscilla Ann a/p Moknasing @ John - Moknasing, Priscilla Ann (2015)
Neurodegenerative diseases have become a global issue affecting various societies around the world. These are mostly classified as an ageing related diseases. Since the cure to these diseases is still a distant goal, prevention of occurrence of neurodegenerative diseases by leading a healthy life as one ages is the most important. In view of this, extensive research is ongoing using traditional knowledge to promote a safe and economical way towards healthy aging. Since, bioactive components from mushrooms and plants have been known to have neuritogenic, neuroprotective, and neurotropic activities, we decided to further investigate these properties. Hence, the aim of this study was to evaluate the effects of L. rhinocerotis mycelium, G. lucidum mycelium, G. neo-japonicum mycelium, G. biloba and L. barbarum hot aqueous extracts and curcumin individually and their combinations on neuritogenic and neuroprotective activities. Hot aqueous extract of L. rhinocerotis and G. biloba gave the highest percentage of neuritogenic activity at 20 μg/ml with 21.10 % and 31.15 % respectively. Since, a low dose combination was preferred in this study, hence, the combination of 20 μg/ml of L. rhinocerotis hot aqueous extract and a low dose of one μg/ml of curcumin was selected with a maximum neuritogenesis of 27.2 %. It is suggested that the combination of L. rhinocerotis enhanced neuritogenic activity of curcumin compared to the extracts treated individually. The neurite outgrowth was also stained positive for neurofilament-200 antibody indicating the extensions in the differentiated cells were of neuronal origin. Subsequently, the hot aqueous extract of L. rhinocerotis at 20 μg/ml, curcumin at one μg/ml of and their combination were further investigated to elucidate mechanisms involved in neuritogenic activity of PC-12 cells. Henceforth, the mechanism was suggested to induce neuritogenesis in PC-12 cells via the MEK/ERK and PI3K/AKt pathways. Finally, cytotoxicity and neuroprotective effect of L. rhinocerotis, medicinal plant extract and their combinations when the cells were subjected to 100 μM H2O2-induced oxidative stress were evaluated. It was found that, hot aqueous extract of L. rhinocerotis, medicinal plant products and their combinations at all concentrations were not toxic to PC-12 cells. The hot aqueous extract of L. rhinocerotis treated individually failed to protect the cells against H2O2- induced oxidative stress. Among the three natural product tested, curcumin individually at 10 μg/ml, protected the cells against H2O2- induced oxidative stress. However, the combinations of L. rhinocerotis and medicinal plant products protected PC-12 cells against H2O2- induced oxidative stress. The highest neuroprotective effect in PC-12 cells was at combination of 20 μg/ml of L. rhinocerotis hot aqueous extract and 10 μg/ml of curcumin with 65.12 %. In conclusion, the extracts tested were not toxic to PC-12 cells and contained neuroactive compounds. Hot aqueous extract of L. rhinocerotis mycelium treated individually and its combination with curcumin, induced neuritogenesis in PC-12 cells via the MEK/ERK and PI3K/AKt pathways. Finally, neuroprotective activity was present when using curcumin individually and also when L. rhinocerotis was combined with all the three medicinal plant extracts. This indicates that hot aqueous extract of L. rhinocerotis mycelium, enhanced neuritogenesis and neuroprotection in PC-12 cells, when combined with hot aqueous extract of G. biloba and L. barbarum and curcumin.